2020
DOI: 10.1002/joa3.12360
|View full text |Cite
|
Sign up to set email alerts
|

Burden of arrythmias in transgender patients hospitalized for gender‐affirming surgeries

Abstract: Background We sought to describe the burden of arrhythmias and their impact on in‐hospital outcomes in transgender patients who underwent gender re‐assignment surgery. Methods The study utilized data from the National Inpatient Sample from January 2012 to September 2015. Results 16 555 adult transgender patients were included in this study. A total of 610 adults developed arrhythmia out of which atrial fibrillation (N = 475, 2.87%) was the most frequent arrhythmia. In‐hospital mortality increased substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Atrial fibrillation was identified as the primary diagnosis in hospitalizations from January 2005 to September 2015 using the International Classifications of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnostic code, 427.31, which has been used in previous studies. 15 , 16 , 17 Temperature-related illness was defined as the occurrence of either cold- or heat-related injuries using ICD-9 codes: Heat-related illness: 9920, 9921, 9922, 9923, 9924, 9925, 9927, 9928, 9929, E9000, E9001, E9009, 4 and Cold-related illness: 9910, 9911, 9912, 9913, 9914, 9915, 9916, 9918, 9919, E9010, E9011, E9018, and E9019. 3 The authors excluded hospitalizations of less than 18-year-olds and extracted demographic data such as age, sex, race, primary insurance payor, and hospital-level data including the region of the country where the hospital is located, hospital bed size for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Atrial fibrillation was identified as the primary diagnosis in hospitalizations from January 2005 to September 2015 using the International Classifications of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnostic code, 427.31, which has been used in previous studies. 15 , 16 , 17 Temperature-related illness was defined as the occurrence of either cold- or heat-related injuries using ICD-9 codes: Heat-related illness: 9920, 9921, 9922, 9923, 9924, 9925, 9927, 9928, 9929, E9000, E9001, E9009, 4 and Cold-related illness: 9910, 9911, 9912, 9913, 9914, 9915, 9916, 9918, 9919, E9010, E9011, E9018, and E9019. 3 The authors excluded hospitalizations of less than 18-year-olds and extracted demographic data such as age, sex, race, primary insurance payor, and hospital-level data including the region of the country where the hospital is located, hospital bed size for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…El segundo caso, una paciente con múltiples factores riesgo cardiovascular (diabetes, hipertensión, tabaquismo), en tratamiento con estrógenos/progesterona y antiandrógenos, presentó múltiples complejos auriculares prematuros y eventualmente FA 29 . Antwi-Amoabeng et al 30 reportaron una incidencia de arritmias del 3.68% en un una cohorte retrospectiva de 16,555 adultos transgénero hospitalizados para cirugía de reafirmación de género. Las arritmias fueron más frecuentes en los hombres trans que en las mujeres trans (p = 0.0029); la FA fue la arritmia más frecuente, seguida de la taquicardia ventricular.…”
Section: Arritmias En Población Transgénerounclassified
“…Antwi-Amoabeng et al reported a 3.68% incidence of cardiac arrhythmias in a retrospective cohort of 16,555 transgender adults hospitalized for gender-affirming surgeries. Among this cohort, arrhythmia occurred significantly more in transmen than in transwomen ( p = 0.0029) and those who were significantly older [ 124 ]. The most common arrythmia was AF (2.87%, lower than the reported 4% incidence in the general surgery population) followed by atrial flutter and ventricular tachycardia.…”
Section: Qtc Variation In Transgender Individualsmentioning
confidence: 99%